Trichoderma dan Gliocladium untuk Mengendalikan Penyakit Busuk Akar Fusarium pada Bibit Kelapa Sawit - Siti Juariyah; Efi Toding Tondok; Meity Suradji Sinaga (Jurnal Fitopatologi Indonesia, 2018)
Trichoderma and Gliocladium for Controling Fusarium Root Rot Disease of Oil Palm SeedlingsFusarium spp. have been reported as the causal agent of common spear rot and crown rot diseases on oil palm.  An effective strategy to control these diseases is not available yet. This research was aimed to find biocontrol agents for effective control of crown rot disease on oil palm seedlings caused by Fusarium spp. The experiment consisted of 3 parts i.e. pathogenicity test of 3 isolates of Fusarium, identification and in vitro test of biocontrol agents, and in planta test of biocontrol agents against Fusarium spp. In vitro test was done through dual culture test and test for volatile compound produced by the biocontrol agents. In planta test was conducted through inoculation of Fusarium spp. into oil palm seedlings growing on medium containing  selected biocontrol agents i.e. Trichoderma harzianum, T. virens, T. inhamatum, and Gliocladium fimbriatum. In vitro test showed that Gliocladium fimbriatum 1 and 2 were inhibited effectively the growth of Fusarium spp. on the dual culture test, whereas T. harzianum Gadingrejo 2 was inhibited effectively the growth of Fusarium spp. on volatile compound test. The application of biocontrol agents was effective to protect oil palm seedlings from Fusarium spp. infection.